An analytical singular element for interface V-shaped notches in Bi-material Kirchhoff plate bending. (July 2017) - Wang, Shan
Highlights: An analytical singular element is constructed for bi-material V-shaped notches. The present analytical singular element is basing on the symplectic eigen-solution. The present analytical singular element can operate at an arbitrarily high order of precision. Stress intensity coefficients for a bi-material notch can be determined directly from the expansion coefficients. Abstract: An analytical singular element with arbitrary high-order precision is constructed basing on the analytical symplectic eigenfunction of a bi-material V-shaped notch in Kirchhoff plate bending. Stress intensity coefficients for a bi-material notch can be determined directly from the expansion coefficients of the eigensolution. The high accuracy of this singular element is demonstrated by numerical examples. The present method is an effective approach for analysis of bi-material V-shaped notches in a Kirchhoff plate.